PENINGKATAN KESEJAHTERAAN MASYARAKAT MELALUI PENERAPAN DAN PEMAHAMAN PRINSIP BISNIS SYARIAH (UMKM) DI DESA BANDAR SETIA - Qori Rizqiah H Kalingga; Maria Kristina Situmorang; Asna Dewi Susanti; Hermanto Sembiring Meliala (JURNAL JUSTIQA, 2022)
This research was conducted to find out how the level of community welfare through the application and understanding of sharia business (MSMEs) in Bandar Setia Village. The purpose of this research is to build and develop the level of economy and productivity of MSMEs. The data used in this study are primary and secondary data obtained by conducting observations, interviews and documentation. The analysis used is descriptive analysis in the form of qualitative research and the object under study is MSMEs around Bandar Setia Village. One of the ways to improve people's welfare is through business in the form of sharia, in this case through analysis of the application and understanding of doing business in sharia in order to get solutions to the main problems of doing business, namely MSMEs. Based on the results of the study, it was found that the level of application and understanding of sharia business in the form of MSMEs in Bandar Setia Village to improve welfare was still low, namely around 65.8% who understood and those who did not understand about 34.2%. The principles applied in doing business in sharia in the form of MSMEs are shiddiq, amanah, and fathonah. Some of the MSMEs in Bandar Setia Village have implemented this sharia business principle, especially in the buying and selling process, but based on the percentage of research, not all MSMEs in Bandar Setia Village apply this sharia business principle. The principles applied in doing business in sharia in the form of MSMEs are shiddiq, amanah, and fathonah. Some of the MSMEs in Bandar Setia Village have implemented this sharia business principle, especially in the buying and selling process, but based on the percentage of research, not all MSMEs in Bandar Setia Village apply this sharia business principle. The principles applied in doing business in sharia in the form of MSMEs are shiddiq, amanah, and fathonah. Some of the MSMEs in Bandar Setia Village have implemented this sharia business principle, especially in the buying and selling process, but based on the percentage of research, not all MSMEs in Bandar Setia Village apply this sharia business principle.